2018
DOI: 10.21733/ibad.457232
|View full text |Cite
|
Sign up to set email alerts
|

Toplumsal Ci̇nsi̇yet Eşi̇tli̇ği̇ Ve Türk Eği̇ti̇m Si̇stemi̇ndeki̇ Yeri̇: Okul Öncesi̇ Öğretmen Adaylarinin Gözünden

Abstract: Araştırmanın temel amacı okul öncesi öğretmen adaylarının toplumsal cinsiyet eşitliğine ve Türk eğitim sistemindeki yerine ilişkin bakış açılarını ortaya koymak ve bu konuda okullarda yaşadıkları deneyimleri betimlemektir. Bu araştırmada nitel araştırma desenlerinden fenomenoloji deseni kullanılmıştır. Araştırmanın çalışma grubunu, Ankara'daki bir devlet üniversitesinde okul öncesi öğretmenliği bölümünde okuyan 16 öğretmen adayı oluşturmaktadır. Araştırmada veri toplama yöntemi olarak görüşme yöntemi kullanılm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Therefore, awareness studies to be carried out earlier are needed to assimilate gender equality in society (Koyuncu Şahin and Çoban, 2019). In this study, the reason why the "Prejudice and Discrimination" course did not affect gender roles attitudes and gender perception may be because it is more difficult for university students to develop attitudes and perceptions through education compared to earlier ages (Koyuncu Şahin et al, 2018). For this reason, there is a need for studies to be carried out mainly with students at earlier ages.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, awareness studies to be carried out earlier are needed to assimilate gender equality in society (Koyuncu Şahin and Çoban, 2019). In this study, the reason why the "Prejudice and Discrimination" course did not affect gender roles attitudes and gender perception may be because it is more difficult for university students to develop attitudes and perceptions through education compared to earlier ages (Koyuncu Şahin et al, 2018). For this reason, there is a need for studies to be carried out mainly with students at earlier ages.…”
Section: Discussionmentioning
confidence: 94%
“…In a study conducted at the high school level, it was found that high school students have educational needs on the concept of gender, gender roles and stereotypes, homosexuality, women's participation in decision-making mechanisms, violence against women, and women's participation in working life and income . Additionally, studies have presented evidence that pre-service teachers hold gender stereotypes and views on gender inequality (Acar-Erdol et al, 2019;Aslan, 2015;Koyuncu Şahin et al, 2018). Moreover, it was seen that similar results were reached through studies with bachelor students as well (Öngen & Aytaç, 2013;Sis-Çelik et al, 2013;Vefikuluçay et al, 2007;Vefikuluçay Yılmaz et al, 2009).…”
mentioning
confidence: 92%
“…When the studies conducted abroad on the subject were analysed; it was determined that studies such as teachers' gender role beliefs in terms of adult individuals and its effect on children's gender roles (Cahill & Adams, 1997), teachers' views on gender stereotypes, beliefs and attitudes (Chen & Rao, 2011;Frawley, 2005;Meland & Kaltvedt, 2019;Varin & Adriany, 2017;Wingrave, 2018) were conducted. In the studies conducted in our country, studies were conducted at different stages of education, with children and prospective teachers of different age groups (Ata Doğan et al, 2018;Bayramoğlu, 2015;Koyuncu Şahin et al, 2018;Özkan, 2009;Ünlü, 2012;Yağan Güder & Alabay, 2016;Yağan Güder & Güler Yıldız, 2016). The lack of a large number of studies on the preschool period and the lack of a measurement tool to reveal the gender roles of preschool teachers in the classroom environment led the researcher to work on this issue.…”
Section: Introductionmentioning
confidence: 99%